2004
DOI: 10.1016/j.jacc.2004.04.049
|View full text |Cite
|
Sign up to set email alerts
|

Time courses and quantitative analysis of atrial fibrillation episode number and duration after circular plus linear left atrial lesions

Abstract: The results obtained in patients with AF treated with circular plus linear left atrial lesions strongly indicate that substrate modification is the main underlying pathophysiologic mechanism and that it results in a delayed cure instead of an immediate cure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(26 citation statements)
references
References 17 publications
1
23
0
2
Order By: Relevance
“…Among the 53 asymptomatic patients, an episode of AF was captured in one patient (2%) during the study period. The lower incidence of asymptomatic AF recurrence, as compared with our series, might reflect the shorter period of follow-up evaluated (one versus three months) and the choice of Oral et al (13) of scanning 30 days of the long-term follow-up rather than 90 days of the short-term follow-up, in which the incidence of AF recurrence is higher (14,15). Clinical implications for anticoagulation.…”
Section: Abbreviations and Acronymsmentioning
confidence: 52%
“…Among the 53 asymptomatic patients, an episode of AF was captured in one patient (2%) during the study period. The lower incidence of asymptomatic AF recurrence, as compared with our series, might reflect the shorter period of follow-up evaluated (one versus three months) and the choice of Oral et al (13) of scanning 30 days of the long-term follow-up rather than 90 days of the short-term follow-up, in which the incidence of AF recurrence is higher (14,15). Clinical implications for anticoagulation.…”
Section: Abbreviations and Acronymsmentioning
confidence: 52%
“…The strength of these observations is strictly hypothesis generating, as the incidence of postablation AF has been shown to increase with an increased frequency and longer duration of post-ablation ambulatory monitoring. 20,21 Despite the limitations of a lack of long-term monitoring to define each patient’s AF burden and a defined antiarrhythmic drug regimen post-LAA ligation, the finding that LAA ligation is correlated with a reduced incidence of AF at 1 year and in the patients with a pacemaker is intriguing and is deserving of further study in a large cohort with systematic monitoring follow-up and multivariable analysis. This concept is supported by data from patients who underwent catheter ablation for the isolation of the LAA during ablation for recurrent AF, and the finding that LAA electrical isolation is associated with an increased probability of maintaining sinus rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] In contrast, some studies showed that the outcome of patients was independent of whether the PVs were isolated and also independent of the number of isolated PVs. 4,6,20,21 Thus, until now there has been a lack of conclusive scientific evidence of whether complete isolation of the PVs is necessary for successful ablation of AF ablation. The Gap-AFGerman AF Competence Network (AFNET) 1 trial was initiated by and performed within the AFNET to test the hypothesis that complete electric isolation of PVs as recorded by a circular catheter within the PVs is superior to incomplete electric isolation.…”
Section: Kuck Et Al Ablation Strategies For Atrial Fibrillationmentioning
confidence: 99%